การกำจัดสารประกอบอินทรีย์ระเหย ด้วยแผ่นฟอกอากาศโดยกระบวนการโฟโตคะตะไลซีส - เทียนฉาย สถิรภิวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The aim of this research was to study the removal of Volatile Organic Compounds : Toluene, Xylene, Ethylbenzene and Mixed VOCs at concentrations 5, 10, 15 and 20 ppm using photocatalytic air filter (Shisen filter). The experiment was condition under continuous condition and batch condition using a chamber with a volume of 0.03 m³. The variable parameters concentration of VOCs, retention time, area air filter and UV light intensity. The results showed using that continuous condition were air filter with area of 0.15 m² fluoresence source at UV light intensity 2.5 µW/cm² retention time 10 minutes for continuous condition and time 180 minutes for batch condition. The results showed continuous condition had lower efficiency and rate constant with higher concentration of VOCs because of continuous concentration fresh feed of pollutant. The highest removal efficiency of Toluene, Xylene, Ethylbenzene and Mixed VOCs were 66% 63% 64% and 44% respectively. Experiment on batch condition slowed higher efficiency and rate constant with higher concentration of VOCs due to extanded reaction time up to 180 minutes. The highest removal efficiency of Toluene, Xylene, Ethylbenzene and Mixed VOCs were 64% 64% 66% and 51% respectively.